Clinical and cardiovascular characteristics from subjects with COVID-19 and viral outbreaks. - Orea-Tejeda, Arturo; Martínez-Reyna, Óscar Ubaldo; González-Islas, Dulce; Hernández-Zenteno, Rafael; Sánchez-Santillán, Rocío; Flores-Vargas, Aimeé; Ibarra-Fernández, Alan; Pérez-García, Ilse; Pineda-Regalado, Justino; Orozco-Gutíerrez, Juan José (Canadian Journal of Respiratory Therapy, 2022)
Introduction: Lower respiratory tract infections remain the deadliest communicable disease worldwide. The relationship between cardiovascular diseases and viral infections is well known; for example, during the AH1N1 influenza pandemic, many patients developed acute cardiovascular disease. In the SARS-CoV2 pandemic, cardiovascular health has again become a challenge, with early reports showing cardiac damage in these patients. Objective: The study aims to describe the clinical characteristics of COVID-19 patients with an emphasis on cardiovascular compromises, compared with past outbreaks of influenza AH1N1, to identify prognostic factors of severity. Methods: A cross-sectional study of 72 subjects with a confirmed diagnosis of COVID-19 was conducted. Subjects were evaluated in two groups: 38 hospitalized patients and 34 patients in the Intensive Care Unit (ICU). Data from different outbreaks of influenza AH1N1 were then compared with this group. Results: The 34 subjects in the ICU had higher levels of high sensible troponin, D dimer, creatinine, and leukocytes compared with the 38 hospitalized subjects. The lymphocytes count was diminished in 85.29% of ICU subjects. When compared with AH1N1 patients, it was found that SARS-CoV2 patients were 10 years older on average. The proportion of overweight and obese SARS-CoV2 patients was double that in the influenza outbreaks. In addition, it was observed that a high number of SARS-CoV2 subjects presented with diabetes mellitus. Conclusion: There were various clinical and severity differences between each of these outbreaks. However, viral respiratory infection diseases such as SARS-CoV2 are a significant risk factor for acute ischemic, functional, and structural cardiovascular complications. The only way to combat this risk is a prevention approach, specifically through vaccines, but also through measures that force drastic changes in health policies to reduce perhaps the worst of pandemics, obesity, and its metabolic consequences.